SIDE EFFECTS OF HEMODIALYSIS IN CHRONIC KIDNEY DISEASE (CKD) PATIENTS WITH ALOE VERA GEL - Maulida Umi Faizah (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2021)
Patients with chronic kidney disease or Chronic Kidney Disease (CKD) really need action that can help replace the role of the kidneys in the body. One of the actions that can be taken is hemodialysis therapy, where this therapy is able to replace kidney function by filtering blood using a special machine at an unaffordable cost. However, hemodialysis also has side effects, one of which is skin problems such as xerosis, dry skin or xerosis, which is a skin disorder caused by loss of lipids and natural moisturizing factors in the stratum corneum. Problems that arise as a result of hemodialysis actions, of course, also require treatment such as providing moisturizers for xerotic skin. The method used in this research is a literature review study. Database searches via Pubmed, Science Direct, Elsevier, Jama, and Google Scholar. Based on searches and case study results from 5 articles, the effectiveness of aloe vera gel has been proven to overcome skin problems through research. It has been proven that aloe vera gel can moisturize the skin because aloe vera gel contains water with a water content of 99% and, besides that, it also contains glucomannans, amino acids, lipids, sterols and vitamins. Aloe vera gel is indeed effective for treating skin problems such as dry skin without having to spend a lot of money, so it can minimize cost overruns in patients undergoing hemodialysis therapy on a regular or even long-term basis. Keywords: Chronic Kidney Failure; Hemodialysis; Xerosis; Aloe Vera Gel